Sabar .-. pasti di cariin kok klo aku hilang
f(x) = x² × 2³ + 6x
f(5) =
f(x) = x² × 2³ + 6x
f(5) =
Penjelasan dengan langkah-langkah:
[tex] \sf{fungsi.}[/tex]
f(x) = x² × 2³ + 6x
f(5) = 5² × (2 × 2 × 2) + 6(5)
f(5) = (5 × 5) × (4 × 2) + (6 × 5)
f(5) = (25 × 8) + 30
f(5) = 200 + 30
f(5) = 230
[tex] \huge \color{c4faf8}{\underbrace{\textsf{\textbf{\color{pink}-{\color{skyblue}{L}{\color{pink}{z}{\color{skyblue}{y}{\color{pink}{n}{\color{skyblue}{n}{\color{pink}{n}{{\color{skyblue}-}}}}}}}}}}}}[/tex]
| FUNGSI |
- f(x) : x² × 2³ + 6x
- f(5) : ...
f(5) : x² × 2³ + 6x
f(5) : 5² × 2³ + 6(5)
f(5) : (5 × 5) × (2 × 2 × 2) + (6 × 5)
f(5) : 25 × (4 × 2) + 30
f(5) : (25 × 8) + 30
f(5) : 200 + 30
f(5) : 230
[answer.2.content]